Job-related affective well-being and its relation to intrinsic job satisfaction. - Sevastos, Peter P. (Curtin University, 1996)
This thesis investigates the structure of job-related well-being; the identification of variables that contribute to either psychological well-being or distress; and the causal connections among elements of job-related well-being and intrinsic job satisfaction.Two large samples (n=3,044 and 3,709) from a white-collar public sector organisation were used to test a four monopolar model of affective well-being, and the two bipolar model (enthusiasm-depression and anxiety-contentment) proposed by Warr (1990). Structural equation modelling (LISREL) was used to test both models, and results strongly supported a monopolar structure of affective well-being (enthusiasm, depression, anxiety and relaxation). Following the testing of the models, canonical correlation analyses related the set of the four affective variables and intrinsic job satisfaction to a set of predictors. The predictors were drawn from Wan's (1994) sub-categories of nine features of jobs that purport to enhance psychological well-being at work. Two dimensions were extracted from this analysis. The first dimension was mainly defined by intrinsic job satisfaction (from the dependent variable set) and supervisory support and skill utilisation (from the independent variable set). The second dimension was defined mainly by anxiety (dependent variable set) and job demands (independent variable set). From these results a model was developed based on the additive influences of the independent variables on the outcome variables (i.e., affective well-being and intrinsic job satisfaction) that helped explain psychological well-being and distress at work. Finally, a model was also developed that assumed a causal direction from intrinsic job satisfaction to affective well-being. Using a longitudinal sample (n=220) these causal relations were tested with USREL. Results supported the hypothesis that intrinsic job satisfaction leads to affective well-being, rather than the alternative model that had the causal connections in the opposite direction. It was also possible to demonstrate with the same data set that one objective organisational variable, namely tenure, affects intrinsic job satisfaction over time, thus arguing against the proposition that intrinsic job satisfaction is dispositional.